A novel α‐glucosidase inhibitor polysaccharide from Sargassum fusiforme. (30th June 2021) - Zhang, Mengqing; Yang, Ruijin; Yu, Shuhuai; Zhao, Wei
Summary: α‐Glucosidase inhibitors, which can inhibit α‐glucosidase to reduce the release of glucose after a mixed carbohydrate diet, has become a key tool in the management of type 2 diabetes mellitus (T2DM). SFP‐1, an α‐glucosidase inhibitor derived from Sargassum fusiforme ( S . fusiforme ), was studied as a food‐derived hypoglycaemic agent. By binding α‐glucosidase and then changing the conformation of the enzyme, SFP‐1 with a mixed inhibition type exerted an excellent inhibitory effect (IC50 value: 0.681 mg mL −1 ). Structural analyses suggested that the average molecular weight of SFP‐1 was 1.61 × 10 5  Da, mainly composed of glucuronic acid, fucose, galactose, glucose, mannose and xylose, and the relative molar ratio was 23.07: 15.17: 7.72: 4.92: 4.04: 1.99. FTIR and NMR analysis suggested that SFP‐1 was an acidic polysaccharide with both α‐type and β‐type glycosidic bonds. S . fusiforme polysaccharide (SFP‐1) has the potential to develop as functional foods and nutraceuticals in T2DM management. Abstract : In this study, a polysaccharide α‐glucosidase inhibitor SFP‐1 derivedfrom Sargassum fusiforme was studied as a food‐derived hypoglycemic agent.